Seasonal incidence of major insect pests in the multi-storey farming of Mahaneem, pulses and castor in south west Haryana: Seasonal incidence of major insect pests in the multi-storey farming of Mahaneem, pulses and castor in south west Haryana - S P YADAV; R P S DESWAL; J S YADAV; BALBIR SINGH; SATYAJEET; NARENDER SINGH (Journal of Oilseeds Research, 2020)
In the present study, no. of insect pest infestation was observed on the Mahaneem (Ailanthus excelsa) plant. The major loss in the form of mean infestation level in castor was observed by red hairy caterpillar, Amsacta moorei (30% defoliation); castor semilooper, Achaea janata (25% defoliation); tobacco caterpillar, Spodoptera litura (55% defoliation) and leafhopper, Empoasca flavescens (20 % leaf infestation). It was noticed that castor shoot and capsule borer Conogethes punctiferalis infestation was only 8 percent capsule damage, however, its damage was 25% on capsule in monocrop of castor. The major infestation in the pulses i.e. urd bean, cowpea and mung bean was observed by spotted pod borer Maruca testulalis 80 percent pod damage, red hairy caterpillar (25% defoliation) and leafhopper Empoasca kerri (27% leaf infestation). It was concluded in the present study that there was no effect on the incidence of insect pests on mahaneem, pulses and castor except castor capsule borer damage. It might be due to least host preference of this insect towards multi-storey farming system plantation. The study proved successful multi-storey farming system of Mahaneem, pulses and castor in reference to insect pests attack in south west Haryana.